2019
DOI: 10.1111/cogs.12732
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Silent Gesture: Cognitive Biases and Rational Inference in Emerging Language Systems

Abstract: Natural languages make prolific use of conventional constituent‐ordering patterns to indicate “who did what to whom,” yet the mechanisms through which these regularities arise are not well understood. A series of recent experiments demonstrates that, when prompted to express meanings through silent gesture, people bypass native language conventions, revealing apparent biases underpinning word order usage, based on the semantic properties of the information to be conveyed. We extend the scope of these studies b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Each condition had a majority order for each event, shown in 7 out of the 10 training trials for that event. In the natural condition, the majority order reflected the natural semanticallyconditioned ordering preference found in experiments 1a and 1b and in previous work (Schouwstra et al, 2019;Schouwstra & de Swart, 2014), such that participants saw a majority order of SOV for the extensional event and SVO for the intensional event. In the unnatural condition, the majority order was the inverse of the natural condition, seeing a majority order of SVO for the extensional event and SOV for the intensional event.…”
Section: Methodssupporting
confidence: 69%
“…Each condition had a majority order for each event, shown in 7 out of the 10 training trials for that event. In the natural condition, the majority order reflected the natural semanticallyconditioned ordering preference found in experiments 1a and 1b and in previous work (Schouwstra et al, 2019;Schouwstra & de Swart, 2014), such that participants saw a majority order of SOV for the extensional event and SVO for the intensional event. In the unnatural condition, the majority order was the inverse of the natural condition, seeing a majority order of SVO for the extensional event and SOV for the intensional event.…”
Section: Methodssupporting
confidence: 69%
“…When people are engaged in silent gesture, and improvise in the absence of a conventional language system, they use semantic cues to structure their utterances, and they will use utterance structure to obtain different semantic interpretations. This semantically conditioned word order regime can be seen as natural word order behaviour, and is rooted in cognitive biases (Schouwstra & de Swart, 2014;Schouwstra et al, 2019), and conventional ordering rooted in the extensional/intensional distinction has not been observed in any existing languages. 7 However, although improvisation occurs in established languages, these languages are crucially different from silent gesture: they are used for communicative interaction and persist through cultural transmission.…”
Section: Summary and Planmentioning
confidence: 92%
“…There is also experimental evidence that suggests that production biases are mirrored in interpretation of silent gesture. In an experiment with SOV and SVO ordered silent gesture strings with ambiguous action gestures, Schouwstra, de Swart, and Thompson (2019) found that participants use constituent order as a cue to distinguish between intensional and extensional events. Participants were more likely to interpret SVO ordered gesture strings (than SOV ordered strings) as intensional events, but the strength of the effect was much less pronounced than for production.…”
Section: Improvisationmentioning
confidence: 99%
See 1 more Smart Citation
“…What we are stressing here is that there is evidence revealing that gesture has a greater potential for ‘bootstrapping’ a communication system than non-linguistic vocalization (e.g. [66,67]). That said, pantomime would certainly have gradually included vocalizations [47], which would have the effect of enhancing the overall message (as we will argue below, vocal communication evolved for complex syntax that, in turn, developed to facilitate persuasive communication).…”
Section: Persuasion Narrative and Pantomimic Communication In Archaic Homininsmentioning
confidence: 89%